Pengaruh Metode Al-Miftah Lil Ulum terhadap Pembelajaran Kitab Kuning di Pesantren Syaichona Cholil Kutai Timur - Sahfitri, Dini; Ihsan, Muh (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
This study aims to analyze the influence of the Al-Miftah Lil Ulum method on the learning of kitab kuning (classical Islamic texts) at Syaichona Cholil Islamic Boarding School in Kutai Timur. The research employed a quantitative approach with data collection techniques including observation, interviews, and questionnaires. The research sample consisted of 25 students who had applied the Al-Miftah Lil Ulum method for one semester. The results showed that the implementation of this method significantly improved students’ understanding of classical Arabic grammar, learning motivation, and their ability to read and explain the contents of kitab kuning. Simple linear regression analysis produced a determination coefficient value of 0.523, indicating that this method contributed 52.3% to the improvement of students’ learning outcomes. Therefore, the Al-Miftah Lil Ulum method is effective and worthy of being further developed in Islamic boarding school environments.